ENVIRONMENTAL QUALITY ANALYSIS DUE TO TIDAL FLOOD IN PASIRKRATONKRAMAT SUB-DISTRICT PEKALONGAN, INDONESIA - Rosida, Eviana; ., Sudrajat; Marfai, Muh Aris (Environment & ecosystem science, 2020)
Pasirkratonkramat Sub-District is located in West Pekalongan District, Pekalongan City, Central Java, Indonesia. This location has been affected by tidal floods since 2016. Tidal floods have caused a decrease in environmental quality. The method used for this research is a descriptive survey research with an ecological approach. This paper presents the quality of the biophysical environment and social quality. The biophysical environment consists of water quality, soil quality, air quality. The water quality showed that Pollution Index (PI) of surface water is 5,15 (medium pollution), PI of Clean water (Residents’ well waters) is 5,09 (medium pollution) and PI of Clean Water is 2,20 (light pollution). Water quality analyzed by parameters Electrical Conductivity, Salinity, BOD, COD, Total Phosphate as P, Chrome (Cr) (VI), Copper Cu, Nitrite as N, Free chlorine, Sulfur as H2S, Oil and fat, Detergent as MBAS, Fecal Coliform, Total Coliform, Chloride, Total dissolved solids (TDS), Water hardness (CaCO3), and Organic substance (KMnO4). The soil of quality decreased because of inundating sea water, the chemical and physical composition cannot support paddy or plants to grow, even they cannot survive because of salinity and decreasing minerals. The air quality showed that the average Temperature Humidity Index (THI) is 28.74 which mean that 100% of subjects feel uncomfortable. Meanwhile the social quality consists of various activities.